Study of Wear Resistance of Cylindrical Parts by Electromechanical Surface Hardening - Marchenko, D.D.; Matvyeyeva, K.S. (Problems of Tribology, 2024)
The work scientifically substantiates the use of an effective technology for increasing the wear resistance of cylindrical parts, using the example of protective sleeves of cantilever pumps, due to electromechanical surface hardening. A review of research was carried out and it was established that the achievement of the highest values of microhardness of the surface layer at a depth of up to 1.2 mm is possible during electromechanical processing of protective sleeves of cantilever pumps. The application of various modes and schemes of electromechanical surface hardening (EMSH) is accompanied by a change in structure and, as a result, an increase in the hardness of the surface layer of the bushings. The actual contact area of the tool roller with the processed surface and the depth of the temperature-deformation effect depend on the physical and mechanical properties of the materials and the pressing force. The formation of a temperature gradient in the hardened zone at a depth of up to 1.2 mm from the surface has been proven. Metallographic analysis of the surfaces of the sleeves treated by EMSH shows the formation of a white layer with reduced etchability and increased hardness in the hardening zones. The results of the X-ray structural analysis confirmed the formation of the martensite phase in the hardening zone. The microhardness of the hardened steel zone increased by 2.6...3.6 times compared to the initial values at a depth of up to 1 mm from the surface, depending on the materials. In the case of their overlap, the alternation of a fully hardened zone, a partially hardened zone, and a self-relief zone is observed. At the same time, the microhardness of steels along the surface depends on the hardening scheme. Wear tests under friction conditions of parts of cantilever pumps paired with stuffing boxes showed that the wear resistance of protective sleeves after EMSH increased by 3.1 times for 45 steel, 1.9 times for U8 steel, 2.5 times for SHKH15 steel, for cast iron by 1.9 times compared to the initial values. The use of U8 steel samples after EMSH, instead of serial bushings made of steel 45, allows to increase the wear resistance of parts by 6.1 times, which allows us to recommend U8 steel for use in the manufacture of protective bushings for console pumps. On the basis of the research, recommendations are given for the application of EMSH for the formation of a surface layer with increased wear resistance of protective sleeves during their production and during repair of console pumps in workshops or service centers of agribusiness companies.